#TITLE_ALTERNATIVE# - 23404008, Meilizar NIM.
Abstract: This research developes a batch-scheduling model with common-due-date at a deteriorating single machine that considers investment in setup reduction and process quality improvement. Setup reduction can minimize batch sizes, which further minimize the holding cost. On the other hand, non-conforming item produced while the system is out-of-control state are greater than those at in-control state. Process quality improvement is done to decrease the non-conforming items. This model can determine setup time after reduction, probability of non-conforming item after process quality improvement, batch sizes and the number of batches which simultaneously minimize total cost and total actual flowtime. Performance measure of batch scheduling problem minimizes total cost which consist of inventory cost, investment cost, and quality cost. This research uses analytical approach in order to find solutions optimally. This research indicates that setup reduction level and process quality improvement level will influence batch sizes. Setup reduction will minimize batch sizes, while process quality improvement maximize batch sizes. Thereby determination of batch sizes considering setup reduction and process quality improvement will be able to answer the trade off between these conflicting total inventory ( holding cost and setup cost) and quality cost. In this research, the model has been tested using several hypothetical numerical examples.